DIVERSITY OF PHYTOPLANKTON IN THE SWAMP AREA OF THE SAWAH VILLAGE, KAMPAR UTARA SUB-REGENCY, KAMPAR REGENCY, RIAU PROVINCE - Suci Rahma Deni; Nur El Fajri; Adriman Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Phytoplankton was sensitive to the environmental changes, and therefore it might be used as bioindicator. A research aims to understand the diversity of phytoplankton in the swamp area of the Sawah Village was conducted on July to August 2018. There were 3 stations with 3 sampling points in each station. Samples were taken 3 times, once/week, in 3 different stations, namely S1 (natural area), S2 (residential area), S3 (around the plantation area). Water quality parameters measured were temperature, brightness, dept, pH, dissolved oxygen, CO2, nitrate and phospate. Phytoplankton found were consisted of 32 species that were belonged to 3 classes, namely Bacillariophyceae (7species), Chlorophyceae (12species) and Cyanophyceae (11 species). Phytoplankton abundance ranged from 662–3,266 cells/L, the species diversity index (H') ranges from 2,7659–3,5726, the dominance index (C) ranges from 0,1161–0,1963 and uniformity index (E) ranges from 0,874 – 0,8122. Water quality parameters values were as follows: temperature 25 - 270C, pH 4 - 5, dissolved O2was 3.7-3.8 mg/L, CO2 was 1.7-2.7 mg/L, nitrate was 0.171 - 0.231 mg/L, and phosphate was 0.144 - 0.219 mg/L.Keywords: Uniformity index, Black water, Peat swamp,Bacillariophyceae, Chlorophyceae